2021
DOI: 10.3892/ol.2021.12990
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑27b‑3p inhibits the proliferation and invasion of cutaneous squamous cell carcinoma by targeting EGFR and MMP‑13

Abstract: Cutaneous squamous cell carcinoma is a common malignant tumor. The aim of the present study was to examine the biological function of microRNA (miR)-27b-3p in cutaneous squamous cell carcinoma (CSCC) and its underlying mechanism. The relative expression levels of miR-27b-3p were determined in A-431, Colo-16 and NHEK/SVTERT3-5 cell lines. The regulatory effects of miR-27b-3p on the proliferation of CSCC cells were evaluated using MTT and colony formation assays. Transwell assays were conducted to examine the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…Consistent with our results, previous reports have indicated a significant association between the expression level of miR‐1236 and the survival of cancer patients 20,29,30 . For example, Liang et al 32 demonstrated that decreased miR‐1236 expression is associated with poor prognosis in breast cancer. Furthermore, the downregulation of miR‐1236 has been correlated with poorer survival of colon cancer patients, and significantly worse survival rates of gastric cancer patients with low expression of miR‐1236 compared with those with high expression have been reported 20,29,30 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our results, previous reports have indicated a significant association between the expression level of miR‐1236 and the survival of cancer patients 20,29,30 . For example, Liang et al 32 demonstrated that decreased miR‐1236 expression is associated with poor prognosis in breast cancer. Furthermore, the downregulation of miR‐1236 has been correlated with poorer survival of colon cancer patients, and significantly worse survival rates of gastric cancer patients with low expression of miR‐1236 compared with those with high expression have been reported 20,29,30 .…”
Section: Discussionsupporting
confidence: 92%
“…Downregulation of miR‐1236 was also found in renal cell carcinoma and correlated with tumor stage, tumor grade and LN metastasis 31 . Other malignancies in which decreased miR‐1236 expression was detected include hepatocellular carcinoma, lung cancer and breast cancer 17,28,32 . The decreased miR‐1236 expression and its association with unfavorable clinical–pathological features in OC patients observed in our current study suggest that miR‐1236 could serve as a potential marker for the diagnosis and prognosis of OC.…”
Section: Discussionsupporting
confidence: 66%
“…Through correlation analysis, expression level analysis and prognostic analysis, we found that hsa-miR-27b-3p was the most likely upstream tumor suppressor miRNA of C1QTNF1. At present, several studies have shown that miR-27b-3p plays the role of a tumor suppressor miRNA ( Sun et al, 2017 ; Liang and Zhang, 2021 ). Based on the ceRNA hypothesis, 143 lncRNAs upstream of hsa-miR-27b-3p/C1QTNF1 were predicted.…”
Section: Discussionmentioning
confidence: 99%